2006
DOI: 10.1080/10473289.2006.10464573
|View full text |Cite
|
Sign up to set email alerts
|

Processes Influencing Secondary Aerosol Formation in the San Joaquin Valley during Winter

Abstract: Air quality data collected in the California Regional PM 10 / PM 2.5 Air Quality Study (CRPAQS) are analyzed to qualitatively assess the processes affecting secondary aerosol formation in the San Joaquin Valley (SJV). This region experiences some of the highest fine particulate matter (PM 2.5 ) mass concentrations in California (Յ188 g/m 3 24-hr average), and secondary aerosol components (as a group) frequently constitute over half of the fine aerosol mass in winter. The analyses are based on 15 days of high-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 51 publications
(72 reference statements)
6
25
0
Order By: Relevance
“…that region decupled from the stable nocturnal boundary layer influenced by previous day surface emissions). Those studies suggested that nighttime nitrate 5 formation within the residual layer was a major contributor to surface-level PM2.5 concentrations (Watson et al, 2001;Brown et al, 2006;Chow et al, 2006;Lurmann et al, 2006, Prabhakar et al, 2017. Studies in other regions of the U.S. have reached similar conclusions regarding the role of nighttime processing aloft as a source of winter soluble nitrate (Stanier et al, 2012;Kim et al, 2014).…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…that region decupled from the stable nocturnal boundary layer influenced by previous day surface emissions). Those studies suggested that nighttime nitrate 5 formation within the residual layer was a major contributor to surface-level PM2.5 concentrations (Watson et al, 2001;Brown et al, 2006;Chow et al, 2006;Lurmann et al, 2006, Prabhakar et al, 2017. Studies in other regions of the U.S. have reached similar conclusions regarding the role of nighttime processing aloft as a source of winter soluble nitrate (Stanier et al, 2012;Kim et al, 2014).…”
Section: Introductionsupporting
confidence: 55%
“…Intense wintertime air pollution from particulate matter affects numerous locations in the United States (Chen et al, 2012;Lurmann et al, 2006) and around the world (Bessagnet et al,2005;Gwaze et al, 2007;Ricciardelli et al, 2017;Wang et al, 2014). In the U.S., pollution from fine particles (PM2.5) has been decreasing in the past decades.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of processes occurring in the aloft RL on NO − 3 (p) surface concentrations is evident in the NO − 3 (p) diurnal variability, specifically the occurrence of a midmorning peak in surface-level NO − 3 (p) . While the midmorning peak has been previously suggested as a signature of nocturnal nitrate production aloft (Watson and Chow, 2002;Brown et al, 2006a;Lurmann et al, 2006;Pusede et al, 2016;Young et al, 2016), the current study makes novel use of vertical profiles of NO − 3 (p) concentrations measured multiple times on individual days to quantitatively illustrate the importance of nocturnal processes on surface concentrations. The analysis shows that the NO − 3 (p) concentration in the morning-time mixed boundary layer can be dominated by nocturnally produced NO − 3 (p) ; vertical mixing in the early morning, which entrains air from the residual layer into the surface mixed layer, has a particularly large impact on the surface concentrations here due to the nocturnal boundary layer being exceptionally shallow.…”
Section: Resultsmentioning
confidence: 99%
“…The PM 2.5 fraction is dominated by ammonium nitrate and carbonaceous aerosol during fall and winter. Sulfur dioxide emissions in the SJV are low (CARB, 2012), but oxides of nitrogen and ammonia emissions are high (Mansell and Roe, 2002), so lower temperatures and higher relative humidities during late fall and winter favor ammonium nitrate formation (Stockwell et al, 2000;Chow et al, 2005b;Lurmann et al, 2006;Chow et al, 2008). PM 2.5 carbonaceous aerosol in the SJV derives from engine exhaust, biomass burning, cooking, and conversion of organic gases to particles (Chow et al, 1992;Strader et al, 1999;Schauer and Cass, 2000;Chow et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%